Directed topological complexity of spheres - Borat, Ayşe; Grant, Mark (Springer Nature, 2020)
We show that the directed topological complexity [as defined by Goubault (On directed homotopy equivalences and a notion of directed topological complexity, 2017. arXiv:1709.05702)] of the directed n-sphere is 2, for all n≥ 1. © 2019, The Author(s).
Keywords: Directed homotopy; Directed spheres; Directed topological complexity